Study on grain growth behavior of new Ni-based powder metallurgy superalloys - ZHANG Ming; TIAN Tian; WANG Yixing; LIU Jiantao (Fenmo yejin jishu)
The grain growth behavior of the fourth generation powder metallurgy (PM) superalloys was studied. The results indicate that the grain growth range is small when the heat treatment temperature is below the γ′ solution temperature, which is similar to the initial microstructure (as-forged, 3~4 μm). However, the grain size greatly increases to 30~40 μm when the heat treatment temperature exceeds the γ′ solution temperature, and there is little difference in grain size at the several temperatures over the γ′ solution temperature. The grain size increases significantly at the initial stage of heat treatment, and no longer changes after a certain holding time. The influence of temperature and time on grain size is related to the pinning effect of γ′ on grain boundary migration. A new model is established by modifying the parameters such as the activation energy for boundary migration (Q), the time exponent (n), and the generalized mobility constant (A0) based on the traditional grain growth model. The determination coefficient (R2) and the mean-square error (MSE) between the predicted and the experimental values are 0.9997 and 0.12 μm, respectively, showing the high prediction accuracy, and the various characteristics of the grain growth curves can also be predicted accurately.